2021
DOI: 10.1016/j.hpb.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

International multicenter propensity score matched study on laparoscopic versus open left lateral sectionectomy

Abstract: Background: Despite a lack of high-level evidence, current guidelines recommend laparoscopic left lateral sectionectomy (LLLS) as the routine approach over open LLS (OLLS). Randomized studies and propensity score matched studies on LLLS vs OLLS for all indications, including malignancy, are lacking.Methods: This international multicenter propensity score matched retrospective cohort study included consecutive patients undergoing LLLS or OLLS in six centers from three European countries (January 2000-December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In the case of left lateral sectionectomies performed on donors with a normal background liver, the frequency of biliary complications, including bile leak, is reported to be 1.4% to 4.3% [ 9 - 11 ]. In addition, van der Poel et al [ 12 ] found that the frequency of severe complications (abdominal fluid collection requiring drainage, bleeding requiring reoperation, respiratory insufficiency, and sepsis) was 13%, and the mortality rate within 90 days was 1%. In our study, there were no severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of left lateral sectionectomies performed on donors with a normal background liver, the frequency of biliary complications, including bile leak, is reported to be 1.4% to 4.3% [ 9 - 11 ]. In addition, van der Poel et al [ 12 ] found that the frequency of severe complications (abdominal fluid collection requiring drainage, bleeding requiring reoperation, respiratory insufficiency, and sepsis) was 13%, and the mortality rate within 90 days was 1%. In our study, there were no severe complications.…”
Section: Discussionmentioning
confidence: 99%